2018
DOI: 10.7150/thno.21492
|View full text |Cite
|
Sign up to set email alerts
|

Drug Release from Phase-Changeable Nanodroplets Triggered by Low-Intensity Focused Ultrasound

Abstract: Background: As one of the most effective triggers with high tissue-penetrating capability and non-invasive feature, ultrasound shows great potential for controlling the drug release and enhancing the chemotherapeutic efficacy. In this study, we report, for the first time, construction of a phase-changeable drug-delivery nanosystem with programmable low-intensity focused ultrasound (LIFU) that could trigger drug-release and significantly enhance anticancer drug delivery.Methods: Liquid-gas phase-changeable perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
155
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(173 citation statements)
references
References 63 publications
11
155
0
3
Order By: Relevance
“…EE = amount of TEM encapsulated in NBs/total amount of added TEM × 100%; LE = amount of TEM encapsulated in NBs/total amount of lipids for NB preparation × 100%. 15…”
Section: Characterization Of G250-tnbsmentioning
confidence: 99%
“…EE = amount of TEM encapsulated in NBs/total amount of added TEM × 100%; LE = amount of TEM encapsulated in NBs/total amount of lipids for NB preparation × 100%. 15…”
Section: Characterization Of G250-tnbsmentioning
confidence: 99%
“…With respect to tumor implantation, 0.15 mL of SMMC-7721 cancer cells (approximately 1 £ 10 7 cells/mL) was subcutaneously injected into the dorsal hindlimb region of the mouse to establish a xenograft HCC model. The tumor volume was calculated as volume = 0.5 £ L £ W 2 , where L and W were the length and width of the tumor, respectively, measured with calipers (Cao et al 2018). Approximately 15 d later, mice with consistent tumor (approximately 5À8 mm long) were selected for further experiments.…”
Section: In Vivo Experimentsmentioning
confidence: 99%
“…In addition, when exposed to US, the cells secreted much more soluble factors that stimulated proliferation, differentiation and migration of peripheral cells (Vezeridis et al 2006;Fung et al 2014b). However, some studies have reported that US cavitation can inhibit the growth of tumor and cancer cells (Huang et al 2012b;Cao et al 2018). All of the aforementioned effects were obtained under ultrasonic conditions; thus, scientists should try to modulate different important parameters of US, for example, PNP (Li et al 2002), PD (Reher et al 2002), PRF (Wang et al 1994) and axial distance of the focus region (Fung et al 2014a), to exert an optimal effect.…”
Section: Plnds Under Us-mediated Gene Therapy In Vivomentioning
confidence: 99%
“…Under the first ultrasound exposure, the first phase‐change triggered drug release and significantly enhanced anti‐cancer effect. According to the report (Y. Cao et al, ), the biological barriers of tumors could be temporarily overcome by post‐formed lipid‐based nanoparticles. The cellular uptake of PLGA‐based nanodroplets (PN) was enhanced by the microjets.…”
Section: Physical‐responsive Nanomedicinementioning
confidence: 99%
“…Schematic diagram of the release of nanodroplets complex triggered by low‐intensity focused ultrasound radiation at different stages. (Reprinted with permission from Y. Cao et al (). Copyright 2018 Ivyspring International Publisher)…”
Section: Physical‐responsive Nanomedicinementioning
confidence: 99%